The prevalence of computer vision syndrome and associated factors among university students in oman: a cross-sectional study - Aysha Almuqrashi; Huda Al-Noumani; Fatema Al-Abri; Hawraa Al-Hinai; Hiba Bani Oraba (BMC Public Health)
Abstract Background Computer Vision Syndrome (CVS) is among the most significant occupational risks of the 21st century, which impacts 70% of all computer users. The study is conducted in Oman to investigate the prevalence of CVS and the associated factors among university students. Methods This cross-sectional study included 293 undergraduate students from nine colleges and used an online self-administered questionnaire. Results The prevalence of CVS among the participants was 73.7%. The most reported extraocular eye symptoms were headache (52.4%) and eye strain and fatigue (45.7%). The results showed that students with uncomfortable seating postures and close-eye screen distance were twice as likely to develop CVS. Students who do not feel that digital technology affects their lifestyle and eye health and do not have a refractive error or wear glasses were less likely to develop CVS. The odds of CVS being present were less likely when consuming most of the screen time in social entertainment than when using the screen for university study. Conclusion This study found a high prevalence of computer vision syndrome that was significantly associated with uncomfortable seating posture, short screen distance, having no refractive errors, perception of minimal impact of digital technology on lifestyle, and using screens for entertainment. The study emphasized the necessity of considering the high prevalence of CVS and associated factors among university students. Therefore, academic institutions must implement comprehensive ergonomic strategies and healthy visual habits to avoid the occurrence of CVS.